Qualitative And Quantitative Analysis Of Organic Acids In Georgian Wine Lees By LCMS/ MS Method: Pharmaceutical Science-Pharmaceutical Analysis - Kirvalidze, Tamar; Murtazashvili, Tamaz; Bakuridze, Lasha; Jokhadze, Malkhaz; Sivsivadze, Koba (International Journal of Life Science and Pharma Research, 2023)
In the XXI century, the interest and demand for natural compounds have increased significantly, compared to the previous period,especially for those natural compounds that have antioxidant, antimicrobial, and anti-inflammatory properties. Accordingly, organic acids arenoteworthy in this direction since studies have confirmed some organic acids’ antioxidant, antimicrobial, and anti-inflammatory effects. It is known thatwine from vine products is one of the rich sources of organic acids. Therefore, the waste products of wine production - including wine lees areinteresting from this point of view. Winemaking is one of the most successful directions of agriculture in Georgia. Many waste products, such as grapepomace, grape seed, and wine lees, accompany wine production. It was the reason to use the waste product - wine lees- to study organic acids.Hence, the research aims to assess the potential of using a currently wasted winery product - Georgian wine lees as a source of biologically activeingredients. The objective of the current study was to identify the biologically active substances (organic acids) in the waste product of winemaking -wine lees obtained from widely distributed grape varieties in Georgia and to determine their quantitative content. By the LC-MS/MS method, weidentified organic acids in 6 samples of wine lees made from different varieties of Georgian grapes (Saperavi, Kisi, Rkatsiteli) and with differenttechnologies (traditional Kakhetian, factory conditions) and determined three main organic acids (tartaric acid, lactic acid, and citric acid) quantitatively.The results of the current research showed that the grape variety and the winemaking technology affect the qualitative and quantitative content oforganic acids in the wine; in particular, three organic acids were found in the Saferavi wine made by the factory method, and 2 organic acids in thewine made by the traditional Kakhetian (Georgia) method. Organic acid’s quantitative content is also different. Also, the content of organic acids in thewine obtained from different varieties of grapes is different. The research showed that the quantitative content of organic acids in Kisi wine Lees ishigher than the other studied varieties. However, the content of organic acids in all three types of wine is significant. The study results support thepotential of using a currently wasted product - Georgian Wine Lees - as a source of biologically active ingredients.